STRATEGI KEBIJAKAN OTONOMI DAERAH DALAM PERCEPATAN PENGARUSUTAMAAN GENDER (PUG) BIDANG PENDIDIKAN - Rodiyah Rodiyah (Faculty of Law, Universitas Diponegoro, 2012)
Abstract Central Java Education Office Report (2007) shows the number of women illiteracy in districts is relatively higher, 16.41% disparity. Year 2008 PUG implement pilot education project in 9 Districts / Cities. Year 2009 budget for Education PUG 3,5 Billion to realize RPJMD on Justice Mission realization of gender equality.Not all SKPD II District has aggregated data. This situation complicates policy-making autonomy to accelerate PUG. PUG implementation of education has been done with related offices and even synergize the state institutions and Universities. Reality PUG data base implementation of education becomes important-the strategic moment as the basic text of the Academic as well as a basic draft regional regulation Gender Responsive education. Keywords: Policy, Local Government, PUG, Education Abstrak Laporan Dinas Pendidikan Propinsi Jawa Tengah (2007) menunjukan angka buta huruf perempuan di kabupaten/kota relatif lebih tinggi, disparitas 16,41%. Tahun 2008 melaksanakan Pilot Proyek PUG pendidikan di 9 Kabupaten/Kota. Tahun 2009 menganggarkan PUG Pendidikan 3,5 Milyard untuk merealisasikan RPJMD pada Misi terwujudnya Keadilan dan kesetaraan gender. Belum seluruh SKPD II Kabupaten/Kota mempunyai data pilah. Keadaan ini mempersulit pembuatan kebijakan otonomi daerah untuk mempercepat PUG. Pelaksanaan PUG pendidikan sudah dilakukan dengan mensinergiskan dinas terkait bahkan lembaga negara dan Perguruan Tinggi. Realita data base pelaksanaan PUG pendidikan menjadi moment penting-strategis sebagai dasar Naskah Akademik sekaligus menjadi dasar Raperda pendidikan Responsif Gender. Kata Kunci: Kebijakan, Otonomi Daerah, PUG, Pendidikan